Atlas of Global Development: A Visual Guide to the World's Greatest Challenges - World Bank (Washington, D.C. The World Bank, 2011)
Published in association with Harper Collins, the completely revised and updated third edition of the Atlas of Global Development vividly illustrates the key development challenges facing our world today. 'This is an excellent, up-to-date source book which will be invaluable for students of, and staff teaching, higher levels of geography... a clear, concise, easily-accessible and well-illustrated volume.' - Geographical Association, United Kingdom.
Description based on print version record.
Keywords: Education; Environment; Governance; Health, Nutrition, and Population; International Economics and Trade; Macroeconomics and Economic Growth; Poverty Reduction; Social Development